PENGARUH ASIMETRI INFORMASI, UKURAN PERUSAHAAN, DAN MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2012) - Rokhmah, Siti Aenur; Adib, Noval (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this research is to provide empirical evidence of the influence of information asymmetric, firm size, and corporate mechanisms on the earnings management. The Information asymmetric was measurde by the relative bid-ask spread, while the firms size was measured by the natural logarithm of the total assets, and the corporate governance mechanisms were measured by two variables the board of independent commissioner and the proportion of managerial ownership. The Earnings management was measured by the discretionary accruals using Modified Jones Model. The population of this research is 108 companies in the manufacturing sector listed in Indonesian Stock Exchange (IDX). The research data were collected from manufacturing companies the financial statement and annual report for the period of 2010 to 2012. Based on purposive sampling method, there are 36 samples used in this research. The research hypotesis were tested using multiple regression analysis. The results of this research show that information asymmetric have positive relationship with the earnings management. Whereas, variable firms size, board of independent commissioner and proportion of managerial ownership have no relationship with earnings management. Keywords: information asymmetric, firms size, corporate governance, earnings management.